2010
DOI: 10.1111/j.1468-3083.2009.03469.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of four prevalent filaggrin mutations (R501X, 2282del4, R2447X and S3247X) in Austrian and German patients with atopic dermatitis

Abstract: Our data confirm and extend the knowledge of the influence of FLG mutations in AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
48
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 21 publications
(53 reference statements)
10
48
2
2
Order By: Relevance
“…However, in our previous study the SCORAD severity index was not statistically different between mutated and non-mutated cases [16]. FLG null mutations predispose to a form of AD that starts in early infancy and persists into adulthood [14,15,17,20,21,22]. In our study, the 5 FLG mutated KC patients had AD starting in early infancy but persisting into adulthood only in 2 patients.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…However, in our previous study the SCORAD severity index was not statistically different between mutated and non-mutated cases [16]. FLG null mutations predispose to a form of AD that starts in early infancy and persists into adulthood [14,15,17,20,21,22]. In our study, the 5 FLG mutated KC patients had AD starting in early infancy but persisting into adulthood only in 2 patients.…”
Section: Discussionmentioning
confidence: 60%
“…The meta-analysis of 24 studies on FLG mutations has confirmed the association with asthma but only in the context of AD [22]. Some studies have also found significantly higher median serum IgE levels among carriers of FLG mutations [11,17,21]. …”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Greisenegger et al studied the four FLG variants R501X , 2282del4 , R2447X , and S3247X in 462 Austrian and German adult AD patients and 402 control individuals [ 30 ]. Mutation carrier status of the combined genotype was not signifi cantly different in patients with asthma compared to patients without asthma (26 % vs. 22 %), OR = 1.27 (0.79-2.05).…”
Section: Other Risk Allelesmentioning
confidence: 97%